UNLAWFUL ACTIONS IN BUSINESS LEGAL ETHICS - Habeahan, Rasman (Jurnal Pilar Keadilan, 2021)
Business is carried out based on agreements made and agreed upon by the binding parties as applicable by law, but this does not always work well. Business processes that involve many aspects often result in losses originating from mistakes of the parties which are called Unlawful Acts. This research analyzes the terms and elements of unlawful acts. By the provisions in Article 1365 of the Civil Code, an unlawful act must contain the following elements: a. The existence of an action b. The act is against the law c. There is an error on the part of the perpetrator d. There is a loss for the victim e. There is a causal relationship between actions and losses. The normative juridical research method was chosen to provide a basic explanation of this unlawful act based on the Civil Code